2005
DOI: 10.2105/ajph.2003.034900
|View full text |Cite
|
Sign up to set email alerts
|

Equitable Child Health Interventions

Abstract: Today, many of the 10 million childhood deaths each year are caused by diseases of poverty--diarrhea and pneumonia, for example, which were previously major causes of childhood death in many European countries. Specific analyses of the historical decline of child mortality may shed light on the potential equity impact of interventions to reduce child mortality. In our study of the impact of improved water and sanitation in Stockholm from 1878 to 1925, we examined the decline in overall and diarrhea mortality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The direct relationship from maternal and child health (MCH) improvements to the alleviation of poverty has long been recognized [ 12 ]. Other key social determinants of health include better schooling [ 11 ], good governance [ 9 ], clean water [ 13 ], and less social inequality [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The direct relationship from maternal and child health (MCH) improvements to the alleviation of poverty has long been recognized [ 12 ]. Other key social determinants of health include better schooling [ 11 ], good governance [ 9 ], clean water [ 13 ], and less social inequality [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, very few studies have looked at how scaling up such interventions differentially impacts different socio-economic groups. A study of the impact of improved water and sanitation in Stockholm from 1878 to 1925 showed a decline in overall mortality and of diarrhea mortality and a leveling out of socioeconomic differences in child mortality due to diarrheal diseases [ 15 ]. Another paper used comparative risk assessment modeling to estimate the reduction in child mortality as a result of improving child nutrition and providing clean water, sanitation, and fuels [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For all relevant peer-reviewed articles, we abstracted data for the following: (1) information on the intervention being evaluated, including type of structural intervention, target populations, and start and end date of the intervention; (2) components of the theory of change (TOC) or causal pathway framework including predictor variables, intermediate variables, and outcomes of interest; (3) components of the evaluation, including type of evaluation (outcome or impact), type of data collected and timeline for data collection, and statistical methods used to analyze evaluation data; (4) study limitations in conducting the evaluation; and (5) reported generalizability of the findings and scalability of the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Structural interventions refer to public health interventions that alter the social, economic, legal, political, and built environment that shapes health processes and outcomes (1, 2). While they have a long history of implementation and have been considered successful in sectors such as water and sanitation (e.g., water purification and latrine construction) (3, 4), structural interventions have only recently drawn attention in the HIV-prevention field. The World Health Organization’s Global Health Sector Strategy for HIV/AIDS 2011–2015 included for the first time the removal of structural barriers as one of its four strategic directions to achieve universal access to HIV prevention, diagnosis, treatment, and care services (5).…”
Section: Introductionmentioning
confidence: 99%